Comprehensive Study on Oil Spills: Causes, Impacts, Detection, and Mitigation Techniques (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Oil spills pose severe threats to marine ecosystems, human health, and global economies. The paper examines oil spill causes, environmental impacts, detection technologies, and mitigation strategies. It also evaluates modern approaches such as remote sensing, AI-enabled spill detection, nanotechnology-based cleanup, and emerging eco-friendly solutions. The findings highlight global challenges and propose sustainable solutions for improved preparedness and response.